Digital Image Processing - Jähne, Bernd (Springer Berlin Heidelberg : Imprint: Springer, 2005)
Since the first edition of "Digital Image Processing" was published in 1991 it has found its way to many desks and classrooms. The book offers an integral view of image processing from image acquisition to the extraction of the data of interest. The discussion of the general concepts is supplemented with examples from applications on PC-based image processing systems and ready-to-use implementations of important algorithms. The sixth edition has been revised and extended. The whole textbook is now clearly partitioned into basic and advanced material in order to cope with the ever-increasing field of digital image processing. In this way, you can first work your way through the basic principles of digital image processing without getting overwhelmed by the wealth of the material and then extend your studies to selected topics of interest. Each chapter now includes exercises that help you to test your understanding, train your skills, and introduce you to real-world image processing tasks. An important part of the exercises is a wealth of interactive computer exercises, which cover all topics of this textbook.